Pulsed laser deposition of single-layer MoS2 on Au(111): from nanosized crystals to large-area films. Issue 2 (31st October 2018) - Tumino, Francesco; Casari, Carlo S.; Passoni, Matteo; Russo, Valeria; Li Bassi, Andrea
Abstract : Molybdenum disulphide (MoS2 ) is a promising material for heterogeneous catalysis and novel 2D optoelectronic devices. In this work, single-layer MoS2 is synthesized on Au(111) by pulsed laser deposition, showing the potentialities of this technique in the synthesis of high-quality 2D materials films. Abstract : Molybdenum disulphide (MoS2 ) is a promising material for heterogeneous catalysis and novel two-dimensional (2D) optoelectronic devices. In this work, we synthesized single-layer (SL) MoS2 structures on Au(111) by pulsed laser deposition (PLD) under ultra-high vacuum (UHV) conditions. By controlling the PLD process, we were able to tune the sample morphology from low-coverage SL nanocrystals to large-area SL films uniformly wetting the whole substrate surface. We investigated the obtained MoS2 structures at the nanometer and atomic scales by means of in situ scanning tunneling microscopy/spectroscopy (STM/STS) measurements, to study the interaction between SL MoS2 and Au(111)—which for example influences MoS2 lattice orientation—the structure of point defects and the formation of in-plane MoS2 /Au heterojunctions. Raman spectroscopy, performed ex situ on large-area SL MoS2, revealed significant modifications of the in-plane E12g and out-of-plane A1g vibrational modes, possibly related to strain and doping effects. Charge transfer between SL MoS2 and Au is also likely responsible for the total suppression of excitonic emission, observed by photoluminescence (PL) spectroscopy.